2011
DOI: 10.1007/s12034-011-0080-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of strontium oxalate crystals in agar–agar gel

Abstract: Single crystals of strontium oxalate have been grown by using strontium chloride and oxalic acid in agar-agar gel media at ambient temperature. Different methods for growing crystals were adopted. The optimum conditions were employed in each method by varying concentration of gel and reactants, and gel setting time etc. Transparent prismatic bi-pyramidal platy-shaped and spherulite crystals were obtained in various methods. The grown crystals were characterized with the help of FT-IR studies and monoclinic sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Sr-oxalate X [187,188] Cd-oxalate X Diamagnetic [189][190][191] CdMgHPO 4 X [192] Ndhepthamolybdate X [193] Lahepthamolybdate X X [194] Cu-succinate X [195] Cu-tartrate Diamagnetic [195] …”
Section: Behavior Referencesmentioning
confidence: 99%
“…Sr-oxalate X [187,188] Cd-oxalate X Diamagnetic [189][190][191] CdMgHPO 4 X [192] Ndhepthamolybdate X [193] Lahepthamolybdate X X [194] Cu-succinate X [195] Cu-tartrate Diamagnetic [195] …”
Section: Behavior Referencesmentioning
confidence: 99%
“…Similarly, crystals of strontium oxalate, an isomorphic compound of weddelite, grew in an agar gel containing strontium chloride and covered with a solution of oxalic acid, both at 2 M (Fig. 3c) (Dalal & Saraf, 2011). Oxalate crystals formed at similar growth rates for all pH values tested, with regular bipyramidal and irregular crystalline shapes, regardless of acidic or basic conditions (Fig.…”
Section: Figurementioning
confidence: 76%
“…According to Bhavsar [34], neutral gel reduce the rate of reaction and control the nucleation, while Patil et al [35] reported that, the neutral gel increase the size of crystals. However Dalal et al [36] found that the neutral gel reduced the number of nucleation, but could not change the size of crystals. In the present study while using the neutral gel, it was observed that, the large numbers of nuclei were found to be grown near the gel-gel diffusion interface.…”
Section: Resultsmentioning
confidence: 96%